FOXP4-AS1 Inhibits Papillary Thyroid Carcinoma Proliferation and Migration Through the AKT Signaling Pathway - Luo, Xue; Gao, Qingjun; Zhou, Tian; Tang, Rui; Zhao, Yu; Zhang, Qifang; Wang, Nanpeng; Ye, Hui; Chen, Xinghong; Chen, Song; Tang, Wenli; Zhao, Daiwei (Frontiers in Oncology, 2022)
Papillary thyroid carcinoma, also known as PTC, is one of the commonest malignancies in the endocrine system. Long non-coding RNAs (lncRNAs) in PTC could maintain proliferative signaling, induce therapeutic resistance, activate invasion and migration, and sustain stem cell-like characteristics. In this paper, results showed that lncRNA forkhead box P4 antisense RNA 1 (FOXP4-AS1) is downregulated in PTC tissues and cell lines. Patients in TCGA cohort with a higher FOXP4-AS1 expression showed a higher disease-free interval (DFI) rate, and the expression of FOXP4-AS1 is shown to be linked to the clinical stage, T stage, N stage, and extraglandular invasion condition of the TC patients. FOXP4-AS1 is localized in the cell cytoplasmic domain of PTC cells. Functionally, upregulated FOXP4-AS1 inhibited PTC cell proliferation, apoptosis, and migration, whereas it downregulated FOXP4-AS1-promoted progression of PTC. In vivo assay also confirmed the tumor inhibitory effect of FOXP4-AS1 in PTC growth. Mechanism analysis indicated that FOXP4-AS1 can play its functions by regulating the AKT signaling pathway, and AKT inhibitor treatment could attenuate the impact of FOXP4-AS1 on PTC progression. Furthermore, FOXP4-AS1 also negatively regulates the expression of its host gene FOXP4. Collectively, we showed that FOXP4-AS1 inhibited PTC progression although AKT signaling and FOXP4-AS1 plays a tumor-suppressor role in PTC tumorigenesis.